332 - Correlating Urinary Tract Infection Risks with Sodium–Glucose Cotransporter-2 Inhibitors: Insights from National Health Insurance Data in South Korea - Jeon, B; Park, J; Bae, J; Tae, B (Continence (Amsterdam), 2025)
This study aimed to investigate the association between the use of sodium–glucose cotransporter-2 inhibitors (SGLT2 inhibitors) and the risk of urinary tract infections (UTIs) in individuals with type 2 diabetes mellitus (T2DM). Although SGLT2 inhibitors offer clinical benefits such as improved glycemic control and cardiovascular outcomes, concerns have emerged regarding their potential to increase UTI risk due to their mechanism of promoting glucose excretion into the urine. To address this, we conducted a large-scale population-based study using data from the National Health Insurance Service (NHIS) of South Korea. We performed a retrospective cohort analysis utilizing NHIS claims data between 2017 and 2018. Adults with T2DM who were already on metformin therapy and initiated either an SGLT2 inhibitor or another oral antidiabetic agent as part of dual therapy were included. Patients with prior recurrent UTIs, significant genitourinary surgery, or advanced renal impairment were excluded. The primary outcome was the incidence of UTIs, identified via diagnostic coding. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs), and Kaplan–Meier curves were generated to evaluate UTI-free survival. Propensity score matching was conducted to balance baseline characteristics between groups. A total of 27,128 patients were included, with 1,274 receiving SGLT2 inhibitors. After matching, the incidence of UTIs was 2.67% among SGLT2 inhibitor users, compared to 3.06% and 3.30% in the sulfonylurea and DPP-4 inhibitor groups, respectively. The HR for UTI incidence in the SGLT2 inhibitor group was 0.874 (95% CI: 0.585–1.309; p = 0.5097), indicating no statistically significant increase in risk. Kaplan–Meier analysis showed no significant difference in cumulative UTI incidence among treatment groups. Although the pharmacologic action of SGLT2 inhibitors increases urinary glucose excretion, which theoretically may foster bacterial growth in the urinary tract, our findings do not support a clinically meaningful increase in UTI risk. Instead, the continuous urinary flow and host defense mechanisms may counteract such risks. Furthermore, longer treatment duration with SGLT2 inhibitors was associated with a reduced incidence of UTIs, suggesting that early concerns may not persist with sustained use. In this real-world, population-based analysis, the use of SGLT2 inhibitors as an add-on therapy to metformin was not associated with an elevated risk of UTIs compared to other commonly prescribed oral antidiabetic agents. These findings support the safety of SGLT2 inhibitors in routine clinical use, though continued monitoring and patient education on UTI symptoms remain important, especially in high-risk populations such as older adults and females. [Display omitted] [Display omitted] [Display omitted] Funding This research was supported by the Basic Science Research Program through the National Research Foundation of Korea (NRF), funded by the Ministry of Science, Information, and Communications Technology (ICT) and Future Planning (NRF-2021R1l1A2060109), and a Korea University Grant. None of the funding agencies had any role in the study concept and design, experiments, data analysis, manuscript writing, or decision to publish. Clinical Trial Yes Public Registry No RCT No Subjects Human Ethics Committee Is this study registered in a public clinical trials registry? Yes Helsinki Yes Informed Consent No